Characterization of large LGAD sensors for proton counting in particle therapy. (1st September 2022) - Villarreal, O.A.M.; Peroglio, G.; Vignati, A.; Giordanengo, S.; Milian, F.M.; Ferrero, M.; Menzio, L.; Abujami, M.; Galeone, C.; Ali, O.H.; Vignali, M.C.; Borghi, G.; et al.
Abstract: A proton counter prototype based on Low Gain Avalanche Detector (LGAD) technology is being developed for the online monitoring of the fluence rate of therapeutic proton beams. The laboratory characterization of thin (45 μm and 60 μm) LGAD sensors segmented in 146 strips with an unprecedented large area of 2.6 × 2.6 cm 2, covering the entire beam cross-section, is presented and discussed. The production includes 14 wafers with different characteristics, designed and produced at Fondazione Bruno Kessler (FBK) of Trento in 2020. The laboratory characterization was carried out at FBK, right after production, and at the University of Torino, after cutting the sensors, using a probe station with a power analyzer for the static DC electrical tests. The tests proved that the production was of very high quality. From 16 sensors randomly selected from different wafers, we observed consistency between the measurements performed at FBK and at the University of Torino, indicating that the cut did not degrade the performance. The sensors were also exposed to the clinical proton beam of the National Center for Oncological Hadrontherapy (CNAO, Pavia, Italy). The results show that LGADs allow achieving, in a very thin active thickness, a good separation between the proton signal, a peak of a very short duration, and the noise. This, combined with the large active area, will allow counting protons delivered with high efficiency at the high rates of a clinical beam.